Trading Systems and Methods - Kaufman, Perry J. (Wiley trading, 2020)
"Trading Systems and Methods, Sixth Edition provides traders, money managers, and trading systems developers with a complete understanding of the tools and techniques needed to develop or choose a trading program for their needs. It begins with a discussion of basic mathematical and statistical concepts including how much data to use, how to create an index, probabilities, and other tools necessary to an understanding of trading systems and methods. Key technical analysis topics and indicators are then covered including identifying trends and momentum. The analytical framework for comparing patterns to other systematic methods and techniques is presented. Examples are provided for stocks, including ETFs and futures. This new edition offers expanded coverage of arbitrage and high frequency trading, along with even more sophisticated risk management models. Trading Systems and Methods, Sixth Edition thoroughly updates this much in demand reference - adding more systems, more methods, and an extensive array of risk analysis techniques necessary to survive and thrive in post-crisis markets. As markets evolve, so must the strategies used to trade them. No one understands this more than Perry Kaufman - one of the world's most respected and trusted trading systems experts. For decades, professional and active individual traders have turned to Trading Systems and Methods for complete information about the latest, most successful indicators, programs, algorithms, and systems"--